Preoperative predictive factors for gallbladder cholesterol polyp diagnosed after laparoscopic cholecystectomy for polypoid lesions of gallbladder - Lee, Hyojin (Ann Hepatobiliary Pancreat Surg, 2016)
BACKGROUNDS/AIMS: We investigated patients' clinical and radiological data to determine preoperative factors that predict cholesterol gallbladder (GB) polyps of large size, which can be helpful for decision on further diagnostic tools. METHODS: In this study, we retrospectively analyzed 126 patients who underwent laparoscopic cholecystectomy for GB polyps >10 mm diagnosed preoperatively by abdominal ultrasonography between February 2002 and February 2016 in Department of Surgery, Sanggye Paik Hospital. Patients were divided into non-cholesterol polyps group and cholesterol polyps group, based on the postoperative pathologic diagnosis. Clinical and radiological data, such as gender, age, body weight, height, body mass index (BMI), laboratory findings, size, number and shape of the polypoid lesions, and presence of the concurrent GB stone were compared between the two groups. RESULTS: Of the 126 cases, 73 had cholesterol polyps (57.9%) and 53 cases were non-cholesterol polyps (42.1%). The younger age (<48.5 years), size of polyp <13.25 mm and multiple polyps were independent predictive variables for cholesterol polyps, with odd ratios (OR) of 2.352 (p=0.045), 5.429 (p<0.001) and 0.472 (p<0.001), respectively. CONCLUSIONS: Age, size and polyp number were used to predict cholesterol GB polyp among polypoid lesions of the gallbladder >10 mm. For cases in which these factors are not applicable, it is strongly recommended to evaluate further diagnostic tools, such as computed tomography, endoscopic ultrasonography and tumor markers.